Molecular Modeling Approach to Determine the Flory‐Huggins Interaction Parameter for Polymer Miscibility Analysis. Issue 13 (25th April 2018) - Callaway, Connor P.; Hendrickson, Kayla; Bond, Nicholas; Lee, Seung Min; Sood, Parveen; Jang, Seung Soon
Abstract: In this work, we present a thorough procedure for estimating the Flory‐Huggins χ‐parameter for use in atomistic and mesoscale molecular simulations in computational materials science. In particular, we propose improvements upon traditional Flory‐Huggins theory by implementing a Connolly volume normalization (CVN). We apply this technique to several test systems, including a blend of poly (epichlorohydrin) and poly (methyl acrylate), a blend of polyethylene glycol and poly (methyl methacrylate), a blend of polystyrene and deuterated polystyrene, and three molecular‐weight variants (monomer, dimer, and trimer) of a triblock copolymer for use in multicompartment micelle applications. Our results demonstrate that the newly developed procedure offers high accuracy and efficiency in predicting the Flory‐Huggins χ‐parameter for miscibility analysis compared to traditional experimental and computational methods. There are still several factors that cause the magnitude of the χ‐parameter to vary between simulations performed on molecular species with the same identity but different degrees of polymerization; although we discuss possible explanations for these factors, this is nonetheless a primary focus for further exploration into this new methodology. Abstract : A method for accurate evaluation for Flory‐Huggins interaction parameter has been developed using molecular modeling techniques. The interaction energy per volume and dielectric screening are the key factors to improve the accuracy in our study.